Effects of previous cyclic loading history on subsequent cyclic hehaviour of sand - Xiangwu Luo; Wen Song (PLoS ONE, 2025)
Sand widely employed as subgrade materials, experience varying traffic-induced cyclic loads during service. This study investigates how prior loading history alters their subsequent cyclic deformation characteristics through multistage drained cyclic triaxial tests. Specimens underwent two-phase loading with controlled stress amplitude variations (increase, decrease, or maintenance) in the second stage. Key findings reveal: 1) Stress history critically governs deformation patterns—increased second-stage amplitude reactivates strain accumulation, while hysteresis loop reopening depends on the cumulative plastic strain from first-stage loading; Hysteresis loop reopening in subsequent loading is governed by whether prior deformation exceeds the first-cycle strain threshold observed in virgin sand under equivalent stress amplitude; A novel deformation model incorporating strain accumulation rates and equivalent cycle numbers quantitatively predicts stress-history effects. The proposed framework advances the mechanistic understanding of sand’s memory-dependent cyclic behavior, providing practical tools for infrastructure design under multistage traffic loading conditions.